2011
DOI: 10.1097/htr.0b013e318218dd3d
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Reasoning Training Years After Traumatic Brain Injury in Adults

Abstract: This study provides preliminary evidence that short-term intensive training in top-down modulation of information benefits gist-reasoning and generalizes to measures of executive function and real life function at chronic stages of post-TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 72 publications
4
69
2
Order By: Relevance
“…The finding of improved synthesising ability is encouraging, since it has not been previously documented that impaired abstraction of complex information skills can be improved years after sustaining a brain injury in those with persistent mild deficits. These findings extend prior work showing that SMART's utilisation of multi-dimensional thinking strategies serves to improve the ability to synthesise information in healthy adults, teens with chronic-stage TBI, and teens living in poverty (Anand et al, 2011;Cook et al, 2014;Gamino et al, 2014;Vas et al, 2011). The present evidence suggests that the SMART programme has the potential to enhance higher-order abstract thinking capacity in adults with mild-spectrum TBI (who constitute the majority of the TBI population).…”
Section: Gist Reasoningsupporting
confidence: 82%
See 2 more Smart Citations
“…The finding of improved synthesising ability is encouraging, since it has not been previously documented that impaired abstraction of complex information skills can be improved years after sustaining a brain injury in those with persistent mild deficits. These findings extend prior work showing that SMART's utilisation of multi-dimensional thinking strategies serves to improve the ability to synthesise information in healthy adults, teens with chronic-stage TBI, and teens living in poverty (Anand et al, 2011;Cook et al, 2014;Gamino et al, 2014;Vas et al, 2011). The present evidence suggests that the SMART programme has the potential to enhance higher-order abstract thinking capacity in adults with mild-spectrum TBI (who constitute the majority of the TBI population).…”
Section: Gist Reasoningsupporting
confidence: 82%
“…In a series of studies, our team has shown that individuals benefit from SMART at multiple levels ranging from cognitive performance to neural function with gains in real-life function when provided with mental strategies to manage complex information/tasks Gamino, Chapman, Hull, & Lyon, 2010). With regard to TBI specifically, SMART yielded significant gains in cognition and daily life skills in individuals with moderate to severe TBI (initial severity of injury) who were experiencing moderate functional deficits at pre-training period (Cook, Chapman, Elliott, Evenson, & Vinton, 2014;Vas et al, 2011). However, it is not known whether top-down SMART training improves cognitive and neural functions in adults with mild-spectrum TBI at chronic stages post-injury, the majority of whom continue to show deficits in complex cognitive everyday life tasks.…”
Section: Reasoning Training In Veteran and Civilian Traumatic Brain Imentioning
confidence: 98%
See 1 more Smart Citation
“…Lastly, our study would provide better understanding of brain and behavior relationships following rehabilitation for chronic TBI if we assessed more appropriate behavioral measures for improvement associated with the SMART program or if we adopted more refined and specialized training program. The SMART is an integrative training that aims to improve multiple domains of cognitive functions such as abstract reasoning, goal management, and selective attention (Vas et al., 2011). The number–letter switching versus motor speed of the trail‐making test measures cognitive processing speed, working memory, and the ability to switch tasks while maintaining a goal (Sánchez‐Cubillo et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both training programs comprised of 12 sessions (1.5 h per session) for 8 weeks with quizzes, homework assignments, and projects conducted in small group settings, comprising of 4–5 participants. Briefly, the SMART group focused on selective attention, abstract reasoning, and other thinking strategies (Vas, Chapman, Cook, Elliott, & Keebler, 2011), and the BHW group focused on education regarding brain structure and function and the effects of sleep and exercise on the brain performance (Binder, Turner, O'Connor, & Levine, 2008). More specifically, the SMART participants were trained to (1) manage information by blocking distractions and irrelevant information and avoid multitasking, (2) increase the ability to understand main ideas and take‐home messages from information, and (3) examine information from different perspectives.…”
Section: Methodsmentioning
confidence: 99%